The Utilization of Colonial Heritage in Local History Learning in Depok City - Alwahid, Ibnu Habib; Wahyudin, Wahyudin; Rahmadi, Darmawan; Ashriana, Khairunisa (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This research aims to develop a historical understanding of the importance of historical heritage as an argument for the memory of Depok itself, especially during the Dutch Colonial period. It reconstructs the historical foundations and continuity of Depok City during the Dutch Colonial period through its historical buildings, interprets the role and contribution of historical buildings from the Dutch Colonial period in the creation of a special character for the new generation of Depok, and formulates a joint policy on efforts to preserve the material heritage of registered historical buildings from the Dutch Colonial period in Depok City. This is a specific historical study on local history that took place in Depok City. Based on the research category, the method used is the historical method with several stages: heuristics, criticism, interpretation, and historiography. After the research was conducted, the findings include: Colonial period buildings in Depok City vary in their physical condition; some are currently well-maintained, neglected, or have been replaced by other new buildings. Second, these buildings can be used to enhance local history and serve as an asset for the Depok region in promoting holiday zones, especially historical tourism.